The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jgs.16377
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health, Diet, and Frailty at Baseline of the Canadian Longitudinal Study on Aging

Abstract: OBJECTIVES: Poor diet due to poor oral health was proposed as a potential mediator of the association between poor oral health and frailty. This study explores the cross-sectional associations between poor oral health, poor diet, and frailty in Canadian adults, aged 45 to 85 years, and then tests whether the expected oral health-frailty association is changed by taking into account the pathway through poor diet. DESIGN: Cross-sectional study. SETTING: The baseline wave of the Canadian Longitudinal Study on Agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Previous studies that assessed the association between oral health and frailty index used a self-reported number of teeth, 21 and the count of self-reported oral health problems. 22 Both studies found significant associations with frailty index.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies that assessed the association between oral health and frailty index used a self-reported number of teeth, 21 and the count of self-reported oral health problems. 22 Both studies found significant associations with frailty index.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, this is the first study to assess the association between self‐rated oral health and frailty index among older adults using a national representative sample. Previous studies that assessed the association between oral health and frailty index used a self‐reported number of teeth, 21 and the count of self‐reported oral health problems 22 . Both studies found significant associations with frailty index.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have demonstrated that older adults with poor oral health had less intake of proteins, vitamins, and fiber [6,37,38]. In addition, poor oral health has been associated with poor diet quality [39] and a less varied diet [40]. Poor quantity and quality of diet can contribute to malnutrition [41].…”
Section: Discussionmentioning
confidence: 99%